Evaluation of bacteriological profile and antibiotic susceptibility pattern of patients with otorrhea in a tertiary care teaching hospital - Panchal, Pankti D.; Patel, Bhaumik V. (International Journal of Research in Medical Sciences, 2017)
Background: Otitis media is very common disease in developing country and if not treated properly can lead to hearing loss and serious neurological complications. Its bacteriology and antibiotic sensitivity varies in different population. Thus knowledge of the microbiological pattern with antibiotic susceptibility is important to deliver efficacious treatment of this disease. So, purpose of the present study was to determine the microbiological profile and antimicrobial susceptibility pattern of isolates from ear discharge in patients of otitis media. Methods: This study was conducted in Department of Microbiology of our institute for duration of one year. A total of 100 patients’ samples visiting ENT OPD were taken who complaining of ear discharge. Identification of organism was done by using standard biochemical reactions and antibiotic susceptibility testing done by using modified Kirby Bauer method as per CLSI guidelines. Results: Majority of the patients were between 21-30 years of age group (28%). The most common organism isolated was Pseudomonas aeruginosa (25.88%), highly sensitive to aminoglycosides and β-lactam + β-lactamase inhibitor (100%) followed by Staphylococcus aureus (21.17%), highly sensitive to aminoglycosides (100%) and fluoroquinolones (72.22%). Conclusions: Knowledge of the pathogenic agents responsible for otitis media and choice of effective antibiotics according to susceptibility pattern will guide the treatment. It also helps in reducing complications of the disease and decreasing emergence of resistance to antibiotics.